2013
DOI: 10.1186/1754-6834-6-1
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and genomic analysis of kraft lignin biodegradation by the beta-proteobacterium Cupriavidus basilensis B-8

Abstract: BackgroundLignin materials are abundant and among the most important potential sources for biofuel production. Development of an efficient lignin degradation process has considerable potential for the production of a variety of chemicals, including bioethanol. However, lignin degradation using current methods is inefficient. Given their immense environmental adaptability and biochemical versatility, bacterial could be used as a valuable tool for the rapid degradation of lignin. Kraft lignin (KL) is a polymer b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

23
329
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 467 publications
(354 citation statements)
references
References 44 publications
23
329
2
Order By: Relevance
“…Based on the present work, Bacillus sp. SHC1 can produce a maximum MnP at 2313.4 U/L, which is higher than for Cupriavidus basilensis B-8 at 1685.3 U/L (Shi et al 2013). However, the MnP activity from Comamonas sp.…”
Section: Bioresourcescommentioning
confidence: 75%
See 4 more Smart Citations
“…Based on the present work, Bacillus sp. SHC1 can produce a maximum MnP at 2313.4 U/L, which is higher than for Cupriavidus basilensis B-8 at 1685.3 U/L (Shi et al 2013). However, the MnP activity from Comamonas sp.…”
Section: Bioresourcescommentioning
confidence: 75%
“…B-9 is at 1250 U/L based on Chen et al (2012). Shi et al (2013) reported that Cupriavidus basilensis B-8 can produce Lac up to 815.6 U/L. Based on the present work, Bacillus sp.…”
Section: Bioresourcescommentioning
confidence: 99%
See 3 more Smart Citations